Perceptions of 'inclusion' and perceived preparedness among school teachers in Sri Lanka - Hettiarachchi, Shyamani; Das, A. (Elsevier Science Ltd., 2014)
This study examined the preparedness of regular and special education teachers in Sri Lanka to teach students with disabilities in an inclusive educational setting. It also explored their perceptions of the term ‘inclusion’ and its applicability to the Sri Lankan context. A total of 75 teachers were surveyed using a two-part questionnaire. In addition, semi-structured interviews were conducted with eight teachers. The interview data was analyzed using Framework Analysis and the quantitative survey data was analyzed using descriptive statistics. Special education teachers indicated higher perceived competence in working with students with special needs compared to general education teachers. Implications for teacher preparation via pre-service and in-service training are discussed.